Gus dan Ning Figur Ideal Santri Milenial: Studi tentang Identitas Sosial Santri Milenial di Pondok Pesantren Al Ikhsan Beji - Nursetiyawati, Puri Septiana (Institute of Research and Public Service Universitas Jenderal Soedirman, 2023)
This paper explains millennial Islamic students' social identity, manifested in the figures of Gus and Ning in Islamic boarding schools. The research examines millennial students' lifestyle, culture, and actions at the Al Ikhsan Beji Islamic Boarding School. The research methodology uses descriptive qualitative methods. The study results show that Islamic boarding schools' social practices experience de-routinization as a response of students to digital technology. This deroutinization began with the modern behavior and lifestyle of Gus and Ning, which spread widely among students and formed a new identity for Islamic students as millennial Islamic students. This identity is manifested in the fashionable style of dress of the students, the ability of the students to speak foreign languages (Arabic and English), the creativity of the students in various Islamic boarding school events, and the behavior of the students in using social media. This research shows that millennial Islamic students' social identity differs from traditional Islamic students. Millennial Islamic students tend to be liberal, while traditional Islamic students are synonymous with conservative traits. Gus and Ning are ideal figures for millennial Islamic students.